Weapons of the tankers American armor in World War II - Yeide, Harry (Battle gear, 2006)
The United States went from almost no armored force to a world-class operation in fewer years than a man could count on the fingers of one hand. This is the story of the armored battalions' equipment, which was designed with incredible ingenuity and produced with unparalleled speed. It is also the story of the valorous Americans who rode the tanks into combat onthe battlefields of World War II.